DEVELOPMENT OF STUDENTS’ COMPETENCE IN THE USE OF LEGAL DOCUMENTS - Khamrakulov Zafarjon Yigitalievich (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents opinions on the development of students’ competence in the use of normative legal documents. The role of new pedagogical technologies and pedagogical conditions in education in the development of students’ competence is analyzed. Opinions are expressed on the development of the legal culture of youth.